2006
DOI: 10.1111/j.1365-2621.2005.tb07164.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Enhancement Effects on Quality Characteristics of Beef Strip Steaks

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: S : S : S : S : Str tr tr tr trip loins w ip loins w ip loins w ip loins w ip loins wer er er er ere r e r e r e r e remo emo emo emo emov v v v ved 48 h postmor ed 48 h postmor ed 48 h postmor ed 48 h postmor ed 48 h postmortem fr tem fr tem fr tem fr tem from beef sides ( om beef sides ( om beef sides ( om beef sides (om beef sides (n n n n n = 20 pairs) to assess the effects of enhance-= 20 pairs) to assess the effects of enhance-= 20 pairs) to assess the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
34
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 20 publications
14
34
3
Order By: Relevance
“…This is important as color has been reported as the most influential factor affecting consumer purchasing decisions within the marketplace, with consumers preferring steaks that are bright cherry-red colored rather than dark or dull red in color (Mancini and Hunt, 2005). Robbins et al (2002), Stetzer et al (2008), andWicklund et al (2005) used trained sensory panelists to evaluate visual color and found results similar to the instrumental color scores reported in the current and previous studies. Though, to date, no studies have evaluated consumer acceptance of the color of enhanced beef.…”
Section: Objective Measuressupporting
confidence: 71%
See 2 more Smart Citations
“…This is important as color has been reported as the most influential factor affecting consumer purchasing decisions within the marketplace, with consumers preferring steaks that are bright cherry-red colored rather than dark or dull red in color (Mancini and Hunt, 2005). Robbins et al (2002), Stetzer et al (2008), andWicklund et al (2005) used trained sensory panelists to evaluate visual color and found results similar to the instrumental color scores reported in the current and previous studies. Though, to date, no studies have evaluated consumer acceptance of the color of enhanced beef.…”
Section: Objective Measuressupporting
confidence: 71%
“…Increased muscle pH as a result of alkaline phosphate enhancement have been previously observed by authors, with increases in pH of 2.90, 2.10, and 7.50% previously reported by Robbins et al (2003b), Baublits et al (2006), andWicklund et al (2005), respectively. Our study reported pH increases of 2.90 to 3.41% for enhanced treatments.…”
Section: Objective Measuresmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, Crouse et al (1989) found that with an increase in Bos indicus inheritance, an increase in shear force values was observed. Previous studies have demonstrated that enhancement lowers shear force values (Wicklund et al, 2006). In addition, differences in shear force values between USDA quality grades have been reported in previous research (Emerson et al, 2013;Garmyn et al, 2011;Hunt et al, 2014) even though no difference in WBSF between SE and TC was observed in our study.…”
Section: Warner-bratzler Shear Forcecontrasting
confidence: 49%
“…Consumer juiciness scores can be positively affected by enhancement Wicklund et al, 2006) as well as other production factors such as diet, demonstrating that a diet in which grains have been included will improve palatability of meat (Muir et al, 1998). Despite the positive effect of enhancement on EHCF and EHSC compared to HCF and HSC, respectively, consumers rated EHCF considerably juicier than EHSC.…”
Section: Wwwmeatandmusclebiologycommentioning
confidence: 94%